2017
DOI: 10.3892/etm.2017.4028
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and angiographically demonstrated coronary artery disease: A meta-analysis

Abstract: Abstract. Coronary artery disease (CAD) is a leading cause of mortality globally. However, the etiology and pathogenesis of CAD are not fully understood. The aim of the present meta-analysis was to estimate the association between the risk of CAD and Helicobacter pylori (H. pylori) infection. A literature search was performed to identify eligible studies published prior to August 14, 2014. Fixed or random effect meta-analytical methods were used to pool the data and perform the subgroup analyses. The effect me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
0
25
0
2
Order By: Relevance
“…11,12 A positive association has been proposed between Helicobacter pylori (H pylori) infection and stroke. 15,16 Given its association with persistent inflammation, H pylori was postulated to play a role in extragastric illnesses that involve inflammation, such as DM, 17 coronary artery disease, 18 and dementia. 15,16 Given its association with persistent inflammation, H pylori was postulated to play a role in extragastric illnesses that involve inflammation, such as DM, 17 coronary artery disease, 18 and dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 A positive association has been proposed between Helicobacter pylori (H pylori) infection and stroke. 15,16 Given its association with persistent inflammation, H pylori was postulated to play a role in extragastric illnesses that involve inflammation, such as DM, 17 coronary artery disease, 18 and dementia. 15,16 Given its association with persistent inflammation, H pylori was postulated to play a role in extragastric illnesses that involve inflammation, such as DM, 17 coronary artery disease, 18 and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 H pylori causes chronic gastritis mostly without symptoms; however, in some people, H pylori causes gastric and duodenal ulcers and even gastric cancer. 15,16 Given its association with persistent inflammation, H pylori was postulated to play a role in extragastric illnesses that involve inflammation, such as DM, 17 coronary artery disease, 18 and dementia. 19 The association between H pylori infection and stroke was addressed previously.…”
Section: Introductionmentioning
confidence: 99%
“…They found no association in the severity of the vessel atherosclerosis score, the Gensini score, and the angiographic severity score between H. pylori ‐positive and negative patients, but a significant correlation between arterial hypertension and H. pylori infection ( P = 0.014). A recent meta‐analysis by Yu et al involving 26 cross‐sectional studies and 3901 patients with Conorary artery Disease (CAD) and 2715 controls reported a significant association between H. pylori infection and CAD, even in the multivariate analysis (OR: 1.42; 95% CI: 1.09, 1.86; P = 0.01). Interestingly, the association was positive in studies from both Europe and the United States.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…A recent meta‐analysis, focused on the association between H. pylori infection and the risk of CAD, diagnosed by coronaro‐angiography, has shown how this association can be age‐ and ethnicity‐dependent. Among 26 studies suitable for the inclusion criteria, the results showed that the risk of CAD increased nearly twofold in patients with H. pylori infection; these data were stronger in younger adults (<60 years old) and a significant association was described in studies from Europe and the U.S.A …”
Section: Metabolic Syndromementioning
confidence: 99%
“…Among 26 studies suitable for the inclusion criteria, the results showed that the risk of CAD increased nearly twofold in patients with H. pylori infection; these data were stronger in younger adults (<60 years old) and a significant association was described in studies from Europe and the U.S.A. 49 Helicobacter pylori is suspected to contribute as an infective character in the complex pathogenic basis of atherosclerosis, and other large-scale studies are needed to support the use of the eradication therapy for H. pylori as a preventive treatment for CAD. Cerebrovascular acute events have been studied in several populations of H. pylori-infected subjects, the last one linked to the presence of obstructive sleep apnea (OSA) and atrial fibrillation-related stroke.…”
Section: Cardiovascular and Cerebrovascular Diseasementioning
confidence: 99%